2005
DOI: 10.1002/nme.1483
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the stress field of particulate reinforced polymeric composites subjected to tension

Abstract: SUMMARYThe aim of the present study is the detailed numerical investigation of the stress/strain distribution in polymeric matrix composites reinforced with spherical inclusions, using the finite element method (FEM). Perfect adhesion between the matrix and the inclusions was assumed and from the computed stress/strain profiles of the system, debonding initiation and propagation can easily be predicted. Analytical models available in the literature may predict the stress/strain distribution within the inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…On a local scale, complex compressive stresses also play a major role in joint technologies (e.g., screw joints, clamping, fastening), in cutting processes and in tribological applications (i.e., friction, wear and scratch processes) also including fretting fatigue loads [1][2][3][4]. Another example for the development of multiaxial local stresses is in the area of polymer matrix composites, in which a multiaxial stress field develops on a local scale around the reinforcing phase, even though the external load applied to the material may be a uniaxial tensile load [5] Considering that the behavior of polymeric materials under tension and compression may differ particularly in the yield and post-yield regime [6][7][8], the need to characterize the whole range of stress states of plastics becomes evident. Moreover, the above examples indicate the importance of a e-mail : michael.jerabek@borealisgroup.com adequate test set-ups in a comprehensive manner and underline the need for appropriate test methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…On a local scale, complex compressive stresses also play a major role in joint technologies (e.g., screw joints, clamping, fastening), in cutting processes and in tribological applications (i.e., friction, wear and scratch processes) also including fretting fatigue loads [1][2][3][4]. Another example for the development of multiaxial local stresses is in the area of polymer matrix composites, in which a multiaxial stress field develops on a local scale around the reinforcing phase, even though the external load applied to the material may be a uniaxial tensile load [5] Considering that the behavior of polymeric materials under tension and compression may differ particularly in the yield and post-yield regime [6][7][8], the need to characterize the whole range of stress states of plastics becomes evident. Moreover, the above examples indicate the importance of a e-mail : michael.jerabek@borealisgroup.com adequate test set-ups in a comprehensive manner and underline the need for appropriate test methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering study of Eshelby [1957] provided expressions for the stresses just outside a spheroidal inclusion. This work was further continued by Tandon and Weng [1986] and Kakavas and Kontoni [2005] who also illustrated that the analytical results were in a good agreement with the finite element analysis. Micromechanical strength conditions can be determined by specifying the stress in the matrix, at the particle-matrix interface, and in the particles, and subsequently applying strength criteria to the matrix and particles and at the interface.…”
Section: 2mentioning
confidence: 63%
“…In particular, the determination of elastic states of an embedded inclusion is of considerable importance in a wide variety of physical and engineering applications. By Eshelby's idea of eigenstrain solutions and equivalent inclusion, a diverse set of research has been reported analytically [3][4][5][6][7] and numerically [8][9][10][11][12][13][14][15][16] . It should be mentioned that the eigenstrain solution can represent various physical problems, where the eigenstrains can correspond to the thermal-mismatch strains, the strains due to the phase transformation, the plastic strains, as well as the intrinsic strains in the residual stress problems [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations using the finite element methods (FEM) [10] , the volume integral methods (VIM) [11][12][13] , or the boundary element methods (BEM) [19] have been conducted for the analysis of engineering problems with the inhomogeneities of various shapes and material properties. The solution scale of the FEM is usually very large since both the matrix and the inhomogeneity should be discretized over their entire solution domains.…”
Section: Introductionmentioning
confidence: 99%